PIDGIN AND CREOLE: UNDERSTANDING THEIR ROLE AND EVOLUTION IN MULTILINGUAL SOCIETIES - Ailsa Amanda Salsabilah; Dorkas Baba Nguda; Enny Dewi Tribuono (Adisam Publisher, 2025)
This study examines Pidgin and Creole languages, exploring their historical development, linguistic characteristics, societal roles, and future prospects. These languages emerged in contexts of trade, colonization, and migration, serving as tools of communication between speakers of different native languages. Over time, they evolved into complex linguistic systems that encapsulate the cultural and historical interactions of their communities. The research underscores the significance of Pidgin and Creole languages in fostering social inclusion, preserving cultural identity, and bridging communication gaps in multilingual societies. Despite their practical and cultural importance, these languages have often been stigmatized and marginalized due to perceptions of inferiority. However, increasing advocacy and recognition highlight their linguistic richness and their role in maintaining cultural diversity. The study identifies key challenges, including language endangerment, lack of institutional support, and the dominance of global languages, which threaten their survival. At the same time, it emphasizes their potential for revitalization through documentation, education, and integration into modern domains such as digital media and creative industries. By addressing these challenges and promoting greater societal acceptance, Pidgin and Creole languages can continue to thrive as vital components of global linguistic and cultural heritage. The findings reinforce the importance of valuing linguistic diversity and ensuring these languages are preserved and celebrated for future generations.